Phenethyl Isothiocyanate Induces Apoptosis Through ROS Generation and Caspase-3 Activation in Cervical Cancer Cells - Shoaib, Shoaib; Tufail, Saba; Sherwani, Mohammad Asif; Yusuf, Nabiha; Islam, Najmul (Frontiers in Pharmacology, 2021)
The latest research shows that current chemotherapeutics are ineffective because of the development of resistance in cervical cancer cells and hence their scope of use is limited. The main concern of researchers at the moment is the discovery of safe and effective anti-proliferative plant chemicals that can aid in the battle against cervical cancer. Previous studies showed the possible anticancer potential of phenethyl isothiocyanate from cruciferous plants for many cancers by targeting various signaling pathways to exercise chemopreventive and therapeutic effects. This provides the basis for studying phenethyl isothiocyanate's therapeutic potential against cervical cancer. In the present study, cervical cancer cells were treated with various doses of phenethyl isothiocyanate alone and in combination with cisplatin. Phenethyl isothiocyanate alone was sufficient to cause nucleus condensation and fragmentation and to induce apoptosis in cervical cancer cells, but evident synergistic effects were observed in combination with cisplatin. In addition, phenethyl isothiocyanate treatment increased the production of intracellular ROS in a dose-dependent manner in cervical cancer cells. Furthermore, investigation of phenethyl isothiocyanate induced mitochondrial reactive oxygen species production and activation of caspases showed that phenethyl isothiocyanate significantly activated caspase-3.